Structural and Functional Models of Vanadate-Dependent Haloperoxidases (VHPO) - R. Maurya, Mannar (Asian Journal of Chemistry, 2012)
The active center of vanadate-dependent haloperoxidases (VHPO) is constituted by vanadate(V) covalently linked to the imidazole moiety of a histitine side-chain of the protein. Vanadium in these enzymes is in a trigonal-bipyramidal environment, with the imidazole-N and an OH– in the axial positions. We have prepared vanadium(V) complexes with ONO and ONN donor ligands that partly model active site structure of vanadate-dependent haloperoxidases. Generally, KVO3 reacts with sodium/potassium salt of ligands in aqueous medium at pH ca. 7.0 to give dioxovanadium(V) complexes with these ligands. Reaction of [VIVO(acac)2] with these ligands followed by aerial oxidation also provides dioxovanadium(V) complexes. The catalytic potential of these dioxidovanadium(V) complexes as mimics for the activity of vanadate-dependent haloperoxidases and oxidation of other organic substrates are also studied.